Investigation of the role of TCF4 rare sequence variants in schizophrenia. Issue 5 (22nd May 2015) - Basmanav, F. Buket; Forstner, Andreas J.; Fier, Heide; Herms, Stefan; Meier, Sandra; Degenhardt, Franziska; Hoffmann, Per; Barth, Sandra; Fricker, Nadine; Strohmaier, Jana; Witt, Stephanie H.; Ludwig, Michael; et al.
Abstract : Transcription factor 4 ( TCF4 ) is one of the most robust of all reported schizophrenia risk loci and is supported by several genetic and functional lines of evidence. While numerous studies have implicated common genetic variation at TCF4 in schizophrenia risk, the role of rare, small‐sized variants at this locus‐such as single nucleotide variants and short indels which are below the resolution of chip‐based arrays requires further exploration. The aim of the present study was to investigate the association between rare TCF4 sequence variants and schizophrenia. Exon‐targeted resequencing was performed in 190 German schizophrenia patients. Six rare variants at the coding exons and flanking sequences of the TCF4 gene were identified, including two missense variants and one splice site variant. These six variants were then pooled with nine additional rare variants identified in 379 European participants of the 1000 Genomes Project, and all 15 variants were genotyped in an independent German sample (n = 1, 808 patients; n = 2, 261 controls). These data were then analyzed using six statistical methods developed for the association analysis of rare variants. No significant association ( P  < 0.05) was found. However, the results from our association and power analyses suggest that further research into the possible involvement of rare TCF4 sequence variants in schizophrenia risk is warranted by the assessment of larger cohorts with higher statistical power to identify rare variant associations. © 2015 Wiley Periodicals, Inc.